Strategies for reducing meat consumption within college and university settings: A systematic review and meta-analysis - Chang, Kenjin B.; Wooden, Alyssa; Rosman, Lori; Altema-Johnson, Daphene; Ramsing, Rebecca (Frontiers in Sustainable Food Systems, 2023)
Introduction Despite the considerable public and planetary health benefits associated with reducing the amount of meat consumed in high-income countries, there is a limited empirical understanding of how these voluntary changes in food choice can be effectively facilitated across different settings. While prior reviews have given us broad insights into the varying capacities of behavior change strategies to promote meaningful reductions in meat consumption, none have compared how they perform relative to each other within a uniform dining context. Methods To address this gap in the literature, we synthesized the available research on university-implemented meat reduction interventions and examined the variations in the success rates and effect estimates associated with each of the three approaches identified in our systematic review. Results From our analyses of the 31 studies that met our criteria for inclusion (n = 31), we found that most were successful in reducing the amount of meat consumed within university settings. Moreover, independent of the number of individual strategies being used, multimodal interventions were found to be more reliable and effective in facilitating these changes in food choice than interventions targeting the choice architecture of the retail environment or conscious decision-making processes alone. Discussion In addition to demonstrating the overall value of behavior change initiatives in advancing more sustainable dining practices on college and university campuses, this study lends further insights into the merits and mechanics underlying strategically integrated approaches to dietary change. Further investigations exploring the persistence and generalizability of these effects and intervention design principles are needed. Systematic review registration https://doi.org/10.17605/OSF.IO/DXQ5V, identifier: 10.17605/OSF.IO/DXQ5V.